Eulerian dynamics of a profiled wheelset on a profiled straight track. (5th August 2014) - Decuyper, M.
This paper is devoted to the adaptation of the Eulerian equations of motion of an idealized model of wheelset, called a 'bicone', to the case of a profiled wheelset on profiled rails. (The equations of the bicone were derived in a previous paper.) We perform the adaptation from the fundamental kinematical relationships, by introducing a modelling coefficient, which is computed numerically by the extended envelope method (Decuyper, 1983a). The equations are then derived following the same procedure as for the bicone, using the same model of creep contact forces. They are linearized around a nominal motion without any slip. The difference between bicone and wheelset appears to be limited to the roll stiffness terms, with a quantitative effect only. The equations presented here are compared to those presented by Wickens (1968). They prove to be different, in that they are able to deal with large conicities, and that they completely take into account the effect of creep on the difference between left and right normal forces. In other respects, the two sets of equations are equivalent.